REPRESENTATIONS OF FOREIGNERS AND JAPANESE NATIONAL IDENTITY AT THE 1964 OLYMPICS IN IDATEN - Pratama, Himawan (UI Scholars Hub, 2021)
The 2020 Olympics are not Tokyo's first experience of hosting the Games. Previously, the city hosted the 1964 Olympics. This historical background generated nostalgia for the 1964 Olympics ahead of the 2020 Olympics. The 1964 Olympics are remembered for exposing Japanese society to various interactions with foreigners, which eventually provided the setting for expressions of Japanese national identity through comparisons between